The Effectiveness of Mindfulness-Based Cognitive Behavioral Therapy Focused on Anger Management in Reducing Bullying Among Male Students - Badpa, Khaled; Alisofi, Allahnazar; Keykha, Habib (International Journal of Education and Cognitive Sciences, 2022)
Purpose: The present study aims to determine the effectiveness of mindfulness-based cognitive behavioral therapy (CBT) focused on anger management in reducing bullying among male middle school students in Chabahar. Methodology: This research employs a quasi-experimental method with a pre-test and post-test design. The statistical population consists of all male middle school students in Chabahar during the 2022-2023 academic year. For the study, a sample of 30 male middle school students from Chabahar, who scored higher on the Illinois Bullying Scale (2001), was randomly selected and divided into two groups: experimental and control (15 students each). The experimental group underwent ten sessions of mindfulness-based CBT focused on anger management, while the control group received no intervention. The Illinois Bullying Scale (2001) was used for data collection, and data analysis was performed using covariance analysis through SPSS 22 software. Findings: The results indicated that the mean bullying scores of the experimental group significantly differed from those of the control group in the post-test stage (p < 0.01). Conclusion: The findings of this study suggest that mindfulness-based CBT focused on anger management can effectively reduce bullying among students